Reduction of automatically maintained self-injurious behavior utilizing noncontingent matched stimuli. (June 2013) - Davis, Tonya N.; Dacus, Sharon; Strickland, Erica; Machalicek, Wendy; Coviello, Laura
<x xml:space="preserve">Abstract</x> Objective: Analyze the effects of noncontingent matched stimulation (NMS) on the self-injurious behavior (SIB) of an eight-year-old boy with autism. Methods: First, a functional analysis was conducted to identify the reinforcers maintaining SIB. Next, an informal preference assessment was conducted to identify a potential object to provide safe matched stimulation. A multielement design was implemented to evaluate the effects of two conditions: (a) noncontingent access to attention and unmatched stimulation (DVD player) and (b) intervention consisting of access to NMS. Results: Results suggested that NMS resulted in a marked decrease of SIB relative to baseline conditions with unmatched stimulation. Conclusions: Findings suggest that unconventional stimuli may provide stimulation similar to that produced by SIB.